THE ROLE OF ITGC IN SUPPORTING FINANCIAL AUDIT - Adrian Adrian; Sakthy Yudha Santri (Jurnal Akuntansi dan Perpajakan Jayakarta, 2020)
ITGC (Information Technology General Control) is generally known as part of the Financial Audit conducted by the External Auditor. Very diverse software from small scale to enterprise class is needed for many companies due to the rapid development of the business. For the external auditors themselves, one of the jobs performed is to conduct regular financial audits in accordance with the needs of their clients. The regulators themselves both OJK and BI as well as other fields in accordance with their business such as BAPEPAM, have also required several regulations that must be considered by each company that uses information technology in supporting its business